Cadmium promotes breast cancer cell proliferation, migration and invasion by inhibiting ACSS2/ATG5-mediated autophagy. (15th March 2021) - Liang, Yidan; Pi, Huifeng; Liao, Lingzhi; Tan, Miduo; Deng, Ping; Yue, Yang; Xi, Yu; Tian, Li; Xie, Jia; Chen, Mengyan; Luo, Yan; Chen, Mingliang; et al.
Abstract: Cadmium (Cd), which is considered a carcinogenic metal, promotes breast cancer (BC) progression, but the precise mechanism remains unclear. Herein, MCF-7 and T47-D cells were treated with 0.1, 1, and 10 μM cadmium chloride (CdCl2 ) for 24, 48 and 72 h. In our study, Cd exposure significantly accelerated the proliferation, migration and invasion of MCF-7 and T47-D cells. Notably, Cd inhibited autophagic flux by suppressing ATG5-dependent autophagosome formation but had no significant effect on autophagosome-lysosome fusion and lysosomal function. The genetic enhancement of autophagy through ATG5 overexpression suppressed the Cd-mediated increases in proliferation, migration and invasion, which indicated a carcinogenic role of autophagy impairment in Cd-exposed BC cells. GSEA and GeneMANIA were utilized to demonstrate that the Cd-induced decrease in ACSS2 expression mechanistically inhibited ATG5-dependent autophagy in BC cells. Importantly, ACSS2 overexpression increased the level of H3K27 acetylation in the promoter region of ATG5, and this result maintained autophagic flux and abolished the Cd-induced increases in proliferation, migration and invasion. We also verified that the expression of ACSS2 in BC tissues was low and positively related to ATG5 expression. These findings indicated that the promoting effect of Cd on BC cell proliferation, migration and invasion through the impairment of ACSS2/ATG5-dependent autophagic flux suggests a new mechanism for BC cell proliferation and metastasis stimulated by Cd. Graphical abstract: Image 1 Highlights: Cd promoted breast cancer cell proliferation, migration and invasion. Cd suppressed ATG5-dependent autophagic flux. Cd inhibited ACSS2 expression and epigenetically regulated ATG5 expression. ACSS2 enhanced H3K27 acetylation in the promoter region of ATG5. Abstract : ACSS2 overexpression increased the level of H3K27 acetylation in the promoter region of ATG5 and abolished Cd-induced breast cancer progression.